Kesadaran Hukum Sebagai Upaya Menguatkan Masyarakat Yang Inklusif Dan Damai Untuk Pembangunan Berkelanjutan - Heru Romadhon, Ahmad; Miarsah, Fajar Rachmad Dwi; Rodhli, Octavina Putri (jurnal.unprimdn.ac.id, 2024)
This study aims to measure the level of legal awareness in society as an effort to strengthen inclusive and peaceful communities to support the achievement of sustainable development goals. The results of the questionnaire involving respondents from various backgrounds showed that 70% of the community had basic knowledge of the law, while 25% felt they did not have adequate access to legal information. Age and education levels influenced the level of legal awareness, with respondents aged 30-45 years and those with higher education showing a better understanding of the law. Law enforcement that was considered uneven was felt by 65% ​​of respondents as a major challenge, while 80% of respondents believed that higher legal awareness could contribute to the achievement of sustainable development. These results indicate an urgent need to improve legal education and socialization, especially for groups who are less exposed to legal information, in order to build a more just, inclusive, and peaceful society.